A novel sliding mode single-loop speed control method based on disturbance observer for permanent magnet synchronous motor drives. (December 2018) - Liu, Xudong; Li, Ke
A novel speed control method based on sliding mode control and disturbance observer is studied for permanent magnet synchronous motor drives. Different from the conventional speed and current cascade control structure in the field-oriented vector control, the new controller adopts the single-loop control structure, in which the speed and quadrate axes current controllers are combined together. First, a multiple-surface sliding mode controller is designed for the speed control system of permanent magnet synchronous motor. Although the sliding mode controller has the strong robustness for the matched disturbance in the system, it still cannot deal with mismatched disturbance effectively, such as external load disturbance and some parameter variations. Thus, the disturbance observer is introduced to estimate the disturbance in the motor, which is designed by combining the proposed sliding mode controller. Finally, the effectiveness is tested under various conditions by both simulation and experiment. The results show that the designed controller has the fast transient response and robustness under different operating conditions.